1995
DOI: 10.1002/anie.199510211
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure, and Reactivity of 1,3,4‐Triphenyl‐4,5‐dihydro‐1H‐1,2,4‐triazol‐5‐ylidene, a New Stable Carbene

Abstract: Stable to 150 °C, the heterocyclic carbene 1 is characterized by the typical reactivity of a nucleophilic carbene. Dihydrotriazole 1 can be prepared by simple thermal decomposition of its methanol adduct. X‐ray crystal structure analysis, ab initio calculations, and reactivity studies confirm the nucleophilic carbene character of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
276
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 539 publications
(287 citation statements)
references
References 28 publications
6
276
0
5
Order By: Relevance
“…[276][277][278] Several of the studies showed that some heterocyclic carbenes become unstable upon heating. 103,168,279 Interestingly, reactions of this type have not been studied until recently. 4.1.1.…”
Section: Rearrangements and Autotransformationsmentioning
confidence: 99%
See 4 more Smart Citations
“…[276][277][278] Several of the studies showed that some heterocyclic carbenes become unstable upon heating. 103,168,279 Interestingly, reactions of this type have not been studied until recently. 4.1.1.…”
Section: Rearrangements and Autotransformationsmentioning
confidence: 99%
“…Rearrangement of N-phosphanylazolylidenes. 168 However, the processes that take place at elevated temperatures in the absence of other reactants have not been studied.…”
Section: а1-4: X = Cf3so3;mentioning
confidence: 99%
See 3 more Smart Citations